2013
DOI: 10.5902/217976927205
|View full text |Cite
|
Sign up to set email alerts
|

O envelhecer e a morte: compreendendo os sentimentos de idosos institucionalizados

Abstract: RESUMO: Objetivo: compreender os sentimentos dos idosos institucionalizados em relação ao processo de envelhecimento e morte. Método: trata-se de uma pesquisa qualitativa, realizada junto a sete idosas que se encontravam institucionalizadas, no mês de julho de 2012. Resultados: a análise das falas possibilitou a construção de três categorias temáticas: Apreendendo o envelhecer, desvelando a morte e sentindo a institucionalização. Algumas idosas entendem o envelhecimento como processo natural e outras não acred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
0
4
0
8
Order By: Relevance
“…In long-stay institutions the elderlies represent a distinct role that they should have, because it can provide the social exclusion of the elderly by having smaller networks of social relationships, less satisfying and engaging in social activities. 3,13 In this sense, the economic question weighs the institutionalization of the elderly in the ILP because families do not have money enough to keep the elderly at home. [14][15] Of the 67,6% of the elderly study participants reported that in ILP they are between 0 and 5 years, 16,2% of the elderly are longer than 11 years and have experienced losses of other companions leaving them conformed to the situation, remaining there until the end of life.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In long-stay institutions the elderlies represent a distinct role that they should have, because it can provide the social exclusion of the elderly by having smaller networks of social relationships, less satisfying and engaging in social activities. 3,13 In this sense, the economic question weighs the institutionalization of the elderly in the ILP because families do not have money enough to keep the elderly at home. [14][15] Of the 67,6% of the elderly study participants reported that in ILP they are between 0 and 5 years, 16,2% of the elderly are longer than 11 years and have experienced losses of other companions leaving them conformed to the situation, remaining there until the end of life.…”
Section: Resultsmentioning
confidence: 99%
“…1 To be private seniors the help of family members, are required to have a formal and professional organization to meet their needs and ease the isolation of elder. [2][3] Modern man tends to feel alone and with an existential emptiness that the elderly this kind of feeling becomes increasingly distressing. 4 For those who reside in long-stay institutions (ILP -in Portuguese) that feeling of living is just another troubling since there is no social or family support established because the elderly care has always been directed without the inclusion of family members or close.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A institucionalização pode gerar na vida do idoso um estágio de depressão, em que eles não sentem mais vontade de viver, percebem que a vida chegou a uma fase em que não há mais o que se fazer (20) . Em alguns casos observam-se sentimentos de revolta, tristeza, angústia e frustração.…”
Section: Eu Me Sinto Inútil Porque Eu Não Posso Andar Não Posso Ajuunclassified
“…Contudo, "ser idoso não deveria ser sinônimo de morte, mas sim de fechamento de um ciclo, de dever cumprido e de realizações durante todo o processo de vida" (20) . Idealmente, a velhice deveria ser encarada como o início de um novo tempo, possibilidade de viver a vida como sempre se desejou.…”
Section: Eu Me Sinto Inútil Porque Eu Não Posso Andar Não Posso Ajuunclassified